Survey on Aqua Robotics Urban Farm System - Raju, Vinutha; Yashaswini, S; Panimozhi, K (International Journal of Computer Sciences and Engineering, 2019)
Aqua Robotics Urban Farm System is an energy efficiency and cost effective way to grow plants, vegetables or flowers using natural process without soil and external nutrients. Aquaponics system is developed by fish and plants in a cyclic system. There are six goals to achieve, our first goal is to automate fish feeder this is possible with the help of a sensor called servo motor. Second goal is to supply excretion of fish to the plants through regular water supply. And this water contains all necessary nutrients that plant can need. Third goal is to use led grow lights instead of sunlight because this an indoor plant farming. Forth goal is to replace the dirty water in aquariums every three months automatically based on PH value. Fifth goal is to upload the sensed data to the Blynk cloud, an IOT analytics platform service that enables us to connect devices whether they are powered by Blynk modules or by other modules. By cloud information we are able to analyze data which in-tern helps in maintenance of an aqua system and also growth of fish and plants. And retrieve those data using telegram bot as a front UI. Sixth goal is to maintain the temperature of water in the aquarium. Our responsibility in this project is achieving all these six goals.